Developing Local Wisdom-Based E-Module in Reading and Writing Course for Tertiary Students in Indonesia - Erni Erni; Fadly Azhar; Aref Vai (STAI Hubbulwathan Duri, 2023)
The lack of local content-based material in Reading and Writing (RW) courses has contributed to tertiary students' low cultural awareness ability in Indonesia. Technology has increased the use of hypermedia text in RW in learning. This study aimed to develop a local-content-based e-module to improve students' cultural awareness in the RW course. The Research and Development (RD) method was applied through the need analysis, product development, field trial, and dissemination steps. Two media experts and two content experts participated in this study. Thirty-three students were selected purposively as the research sample. Questionnaires using a Likert scale of 1-4 and interviews were used to collect the data. Descriptive statistics and one-to-one analysis were applied in this study. The research found that the media expert validity score was 95%, the content expert validity score was 95%, and the students' validity score was 90%. It means that the e-module was very valid. It was also interpreted that 89% of students were motivated to learn RW course using a local wisdom-based e-module, and 90% agreed that the local wisdom-based e-module improved their cultural awareness. Tertiary students in Indonesia could use an e-module based on local wisdom, especially in RW courses.